EFEKTIVITAS KOMIK TERHADAP HASIL BELAJAR SISWA MATERI PENCEMARAN LINGKUNGAN SMP NEGERI 1 AIR BESAR - Noning, Noning; Syamswisna, Syamswisna; Marlina, Reni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the effectiveness of comic media on student learningoutcome in material environmental pollution in grade VII SMP Negeri 1 Air Besar Kabupaten Landak. The method of this research is Quasi-Experimental Design with Nonequivalent Control Group Design. The study sample consists of two classes namely grade VIIA as class experiment and grade VIIB  as grade control. The sampling technique is intact group. The sampling technique is intact group. Instruments used in this research is 20 items of multiple choice test. The average student learning outcomes are taught using the medium comic is 16.17  higher compared to the average student learning outcomes are taught using the media charta is 14.33. After doing analysis with U Mann-Whitney test, it is resulted that Zcount < Ztabel (-3.80 < -1.96) thus it can be concluded that is significance between the average score of students which were taught by using comic media an charta. Based on the calculation of effect size of 1.20 means the effectiveness of learning by using comic media on environmental pollution material is high and can improve student learning outcomes by 38.49%.Keywords: Effectiveness, Comic Media, Learning Achievement, Environmental Pollution